2017
DOI: 10.1021/acs.est.7b01252
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary Polycyclic Aromatic Hydrocarbon Metabolite Associations with Biomarkers of Inflammation, Angiogenesis, and Oxidative Stress in Pregnant Women

Abstract: Environmental exposure to polycyclic aromatic hydrocarbons (PAHs) is prevalent and may adversely impact pregnancy and development of the fetus. The purpose of this exploratory study was to examine urinary PAH metabolites in association with mediators of these outcomes. To do so we measured a panel of 12 inflammatory, angiogenic, and oxidative stress biomarkers in plasma or urine from women in their third trimester of pregnancy (n=200). Urinary PAH metabolites were highly detectable (>88%) in the study populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 48 publications
7
40
0
Order By: Relevance
“…48 Effects of exposure to PAHs may start prenatally, as suggested by associations between maternal PAH exposure and childhood obesity. 49 Urinary PAH metabolites are associated with higher levels of markers of inflammation and oxidative stress during pregnancy, 50 indicating potential systemic impacts of PAH exposure that could impact pregnancy and development. Emerging evidence that PAHs may alter levels of reproductive hormones in umbilical cord sera 51 provides a further link between maternal exposures and potential prenatal impacts.…”
Section: Discussionmentioning
confidence: 99%
“…48 Effects of exposure to PAHs may start prenatally, as suggested by associations between maternal PAH exposure and childhood obesity. 49 Urinary PAH metabolites are associated with higher levels of markers of inflammation and oxidative stress during pregnancy, 50 indicating potential systemic impacts of PAH exposure that could impact pregnancy and development. Emerging evidence that PAHs may alter levels of reproductive hormones in umbilical cord sera 51 provides a further link between maternal exposures and potential prenatal impacts.…”
Section: Discussionmentioning
confidence: 99%
“…All exposure analytes were measured in urine samples by NSF International in Ann Arbor, MI. Quantification of individual toxicants and analytes followed protocols developed by the Centers for Disease Control and Prevention [44][45][46][47] . We used high-performance liquid chromatography-electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) to quantify a total of nine phthalate metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, urinary 8isoprostane (8-iso-PGF2α), the terminal product of cell membrane lipidperoxidation with strong chemical stability, could reflect oxidative damage of lipids [18,19]. Both epidemiology and toxicology studies have observed elevated levels of oxidative damage along with PAH exposure [12,18,20].…”
Section: Introductionmentioning
confidence: 99%